An unusual case of esophageal and laryngotracheal atresia - Korkmaz, Ayşe; Talim, Beril; Tekinalp, Gülsevin; Aliefendioğlu, Didem; Şenaylı, Atilla; Göğüş, Safiye (The Turkish Journal of Pediatrics, 2002)
Esophageal atresia with or without tracheoesophageal fistula is a relatively common congenital anomaly. However, esophageal atresia with associated laryngotracheal atresia, double tracheoesophageal fistula and cardiac malformations is an extremely rare condition. In this article we report a newborn infant with severe respiratory distress at birth who had both esophageal and laryngotracheal atresia with congenital cardiac malformations, in an attempt to bring attention to the clinical presentation, and emergent diagnostic and therapeutic approaches.